2017
DOI: 10.1111/joes.12195
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Repression‐liberalization Debate: Taking Stock, Looking for a Synthesis

Abstract: Financial repression and liberalization became the object of fierce debates between academics and policy makers since the early 1970s. As of the late 1980s, financial liberalization became also part of the 'Structural Adjustment Programs' sponsored by the International Monetary Fund and the World Bank. However, the literature on financial repression and liberalization remains controversial on its theoretical conclusions and policy implications. Given its importance for both the theory and policy of economic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…The creation and innovation of financial institutions, financial services, financial products, and financial derivatives force the saving-investing cycle to perform more efficiently. However, from a Keynesian perspective, e.g., (Studart 1993;Loizos 2018;Xu and Gui 2019), a more expanded financial system with various participations can reduce the power of the governments in terms of managing the economy. Loosened regulation and supervision on the financial system create a risk of instability and an open-to-attack system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The creation and innovation of financial institutions, financial services, financial products, and financial derivatives force the saving-investing cycle to perform more efficiently. However, from a Keynesian perspective, e.g., (Studart 1993;Loizos 2018;Xu and Gui 2019), a more expanded financial system with various participations can reduce the power of the governments in terms of managing the economy. Loosened regulation and supervision on the financial system create a risk of instability and an open-to-attack system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As bank competition is increased and interest rates go down, borrowers may have an incentive to end long-lasting relationships with their banks. When 1 See Loizos (2017) for a recent review of the financial repression-liberalization debate.…”
Section: Financial Development and The Pros And Cons Of Financial Libmentioning
confidence: 99%
“…Other studies found instead that financial liberalization reduces significantly the likelihood of a crisis (Loizos, 2018;Lee, Lin, and Zerng 2016;Barrell, Karim, and Ventouri 2017); and that financial liberalization has a destabilizing effect in the short run, but over time promotes institutional improvements and more stable conditions (Kaminsky and Schmuckler 2002).…”
Section: The Impact Of Liberalization On the Risk Of Crisismentioning
confidence: 99%
“…A few studies have provided "meta-analyses" (deep surveys) aimed at summarizing, and taking stock of, the results of a large number of previous studies (Bumann, Hermes, and Lensink 2013;Arestis, Chortareas, and Magkonis 2015;Valickova, Havranek, and Horvath 2015). Loizos (2018) attempted a synthesis of the decade-long debate on these issues and argued that it could be found in the "Post-Keynesian attempt to take an institutional perspective within a globalized financial and economic environment." The jury is still out.…”
Section: Other Studiesmentioning
confidence: 99%